Hubungan Faktor Psikologis Terhadap Kinerja Radiografer Rumah Sakit - Amen Desina Sari; Djazuly Chalidyanto (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2016)
Performance is a depiction on achievement rate of an activity, programs or policy in fulfilling target, goals,  vision and mission. In 2012-2014, the number of x-rays damage film in Husada Utama’s Hospital was increase (2.59%). To minimize the loss, Husada Utama Hospital needs correction effort. This research aims to analyze the correlation between psychological factors with radiographer’s performance in radiology unit at Husada Utama Hospital Surabaya. This research is descriptive with cross sectional design. The independent variable on this research is psychological factors while the dependent variable is performance. The analysis unit in this research calculated total sampling of radiographer. Data were obtained from questioners to all the radiographer was 12 people who practice in Husada Utama Hospital using an instrument that has been tested for validity and reliability. The result showed that are psychological factors that respondent have high perception on patient caring (75%), 75% respondent have good attitude, 100% respondent have type A personality, respondents had high learning ability (83,3%),almost all respondents (91,7%) have work stress, Psychological factors correlate with the high performance that showed by respondents (80%).Keywords: Performance, physiological factor, psychological factor, radiology unit